1996
DOI: 10.1021/je960130g
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Partial Molar Volumes of Tetra-n-alkylammonium Bromides in Dimethyl Sulfoxide + Water Mixtures at 298.15 K

Abstract: Partial molar volumes at infinite dilution, , are reported for tetra-n-alkylammonium bromides, R4NBr (R = Me to Pen) in x dimethyl sulfoxide + (1 − x) water mixtures, up to x = 0.1587, at 298.15 K. A linear dependence between of the electrolyte and the molecular weight of the tetraalkylammonium cation was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For DTABr, these two contributions can be evaluated from volume data for tetraalkylammonium bromides (R 4 NBr, with R = methyl [Me], n-butyl [Bu], n-pentyl [Pen]) in DMSO-water solvents [46,60]. The partial molar volumes of DTABr can be calculated, assuming the additivity of the volumes of each chemical group, using the following equations: where V 1 R is the partial molar volume at infinite dilution of R 4 NBr;…”
Section: Solvation Of the Free Monomermentioning
confidence: 99%
“…For DTABr, these two contributions can be evaluated from volume data for tetraalkylammonium bromides (R 4 NBr, with R = methyl [Me], n-butyl [Bu], n-pentyl [Pen]) in DMSO-water solvents [46,60]. The partial molar volumes of DTABr can be calculated, assuming the additivity of the volumes of each chemical group, using the following equations: where V 1 R is the partial molar volume at infinite dilution of R 4 NBr;…”
Section: Solvation Of the Free Monomermentioning
confidence: 99%
“…In this work, we report not only the liquid phase static relative permittivities of water + dimethyl sulfoxide over the entire mole-fraction range under pressures up to 300 MPa at 298.15 K but also the newly-determined static relative permittivities for water + acetone under the same conditions. In addition, we correlate r values with pressure P by use of the Tait-type equation and we evaluate (∂ ln r /∂P) T and r -2 (∂ r /∂P) T values at 0.1 MPa, which are important for analyzing the thermodynamic properties of electrolyte solutions; some limiting partial molar volumes of electrolytes in water + acetone mixtures (Kawaizumi et al, 1988) and in water + dimethyl sulfoxide mixtures (Garcia-Paneda et al, 1996) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results exhibit linearity for both eqs 2 and 3 through a large range of molalities, which is consistent with previous studies of symmetrical quaternary ammonium salts in both aqueous and nonaqueous solvents. 2,[8][9][10]21,[24][25][26] The slopes B v and B v ′ agree for each solvent to within experimental error.…”
Section: Discussionmentioning
confidence: 98%